Improving JavaScript Learning Engagement with Gamification Techniques - Wendyanto Wendyanto; Wirawan Istiono (DRPM - ITB, 2026)
JavaScript is highly demanded in modern development, but traditional learning methods often fail to engage students. To address this, this study designed and developed a responsive, gamified web-based JavaScript learning application using the ReactJS library. The application integrates gamification elements such as dashboards, learning modules, challenges, points, levels, ranks, and achievements to enhance learning engagement. The application’s usability and acceptance were evaluated using the Technology Acceptance Model (TAM) through a survey involving 35 participants. The evaluation yielded a Perceived Usefulness score of 90.00% and a Perceived Ease of Use score of 89.71%, resulting in a high overall average score of 89.85%. These results indicate that respondents strongly agree that the application is highly useful for escalating learning motivation and is easy to use. While the TAM results confirm high user acceptance and demonstrate that gamification effectively eases the JavaScript learning process, our future research will incorporate objective cognitive assessments to definitively measure its absolute pedagogical effectiveness.